2017
DOI: 10.1088/1361-6528/aa7d9d
|View full text |Cite
|
Sign up to set email alerts
|

Optical anisotropy in vertically oriented TiO2nanotube arrays

Abstract: Nanofabricated optically anisotropic uniaxial thin films with deep submicron feature sizes are emerging as potential platforms for low-loss all-dielectric metamaterials, and for Dyakonov surface wave-based subwavelength optical confinement and guiding at interfaces with isotropic media. In this context, we investigate the optical properties of one such uniaxial platform, namely self-organized titania nanotube arrays (TNTAs) grown by the bottom-up nanofabrication process of electrochemical anodization on silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 85 publications
(91 reference statements)
1
16
0
Order By: Relevance
“…The plot (inset) shows Raman peaks corresponding to the TiO 2 rutile phase at 270 and 607 cm –1 , while that of the anatase phase at 152 and 424 cm –1 . These observations are consistent with the Raman spectra reported for TiO 2 nanotubes grown on Kapton and Si wafer substrates. , Furthermore, the Raman spectra also support the XRD data reported for the samples, in which both rutile and anatase phases were observed.…”
Section: Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The plot (inset) shows Raman peaks corresponding to the TiO 2 rutile phase at 270 and 607 cm –1 , while that of the anatase phase at 152 and 424 cm –1 . These observations are consistent with the Raman spectra reported for TiO 2 nanotubes grown on Kapton and Si wafer substrates. , Furthermore, the Raman spectra also support the XRD data reported for the samples, in which both rutile and anatase phases were observed.…”
Section: Results and Discussionsupporting
confidence: 90%
“…These observations are consistent with the Raman spectra reported for TiO 2 nanotubes grown on Kapton and Si wafer substrates. 38,39 Furthermore, the Raman spectra also support the XRD data reported for the samples, in which both rutile and anatase phases were observed. The FTIR spectra of the TiO 2 nanotubes before and after the solvothermal process are shown in Figure 9.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Those short nanotubes are very beneficial in ensuring fast charge carrier transport properties. , Liu et al concluded that the shorter the nanotubes, the faster the electron transport process and the higher photocatalytic performance. However, the observed increase in the fabricated nanotube diameter can be related to the unusual feature of the EG-based electrolytes that result in open and large pore size nanotube arrays. The cross-sectional images of the samples anodized at voltages below or higher than 50 V showed no tubular formation, revealing that the voltage is another key factor for the formation of NTs (Figure S2). Moreover, it was noticed that increasing the anodization time resulted in a rubble layer on the surface of the NTs.…”
Section: Resultsmentioning
confidence: 99%
“…66 Some semiconductor metal oxides, typically TiO 2 , have also been employed, owing to their ability to absorb light and drive photocatalysis. Examples include uniaxial TiO 2 nanotube arrays (pore diameter of 50 nm) to attain anisotropic optical properties 67 and TiO 2 -rGO composite layers (pore diameter of 95 nm) for efficient solar energy conversion. 68 One widely studied material is anodized aluminum oxide with a honeycomb-like structure, synthesized via electrochemical dissolution.…”
Section: ■ Nanoconfinement Architecturementioning
confidence: 99%